The role of non-governmental organisations in NTD programmes - Bush, Simon (Henry Stewart Talks, 2019)
Evolution of NGDO interest in NTD programmes, Role of NGDOs in NTD programmes, Challenges of working in areas in conflict, Challenges of cross border issues, Case study of the NTD NGDO network